2011
DOI: 10.1088/0953-8984/23/18/184105
|View full text |Cite
|
Sign up to set email alerts
|

Molecular transport and flow past hard and soft surfaces: computer simulation of model systems

Abstract: Abstract. The properties of polymer liquids on hard and soft substrates are investigated by molecular dynamics simulation of a coarse-grained bead-spring model and dynamic single-chain-in-mean-field (SCMF) simulations of a soft, coarse-grained polymer model. Hard, corrugated substrates are modelled by an FCC LennardJones solid while polymer brushes are investigated as a prototypical example of a soft, deformable surface. From the molecular simulation we extract the coarse-grained parameters that characterise t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
41
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(49 citation statements)
references
References 161 publications
(325 reference statements)
8
41
0
Order By: Relevance
“…For polymer-liquid interactions the parameter was set to ε pl = 1/3ε, representing the chemical incompatibility between species. Rough surfaces with similar interaction potential and ε pl parameter have been studied previously [46][47][48][49], resulting in highly hydrophobic substrates and yielding to contact angles θ ∼ 120 o for droplets deposited over that surfaces. The rigidity of the polymers is imposed by a harmonic potential…”
Section: Model and Simulation Techniquesmentioning
confidence: 99%
“…For polymer-liquid interactions the parameter was set to ε pl = 1/3ε, representing the chemical incompatibility between species. Rough surfaces with similar interaction potential and ε pl parameter have been studied previously [46][47][48][49], resulting in highly hydrophobic substrates and yielding to contact angles θ ∼ 120 o for droplets deposited over that surfaces. The rigidity of the polymers is imposed by a harmonic potential…”
Section: Model and Simulation Techniquesmentioning
confidence: 99%
“…The flow of simple liquids over flat substrates is often described by the no-slip boundary condition, δ = 0 36 , and the hydrodynamic position, z h , often coincides with the location of the sharp solid-liquid interface, as intuitively expected. Finite slip has been observed in complex liquids 24,34,[37][38][39] or at specific substrates: superhydrophobic 4,13,14,[40][41][42] and chemically patterned ones 43,44 .…”
Section: Navier's Slip Condition and Computational Techniquesmentioning
confidence: 99%
“…We implement a Dissipative Particle Dynamics (DPD) code [18][19][20][21] with explicit solvent and numerically analyse the dynamics of a linear flexible homo-disperse polymer brush subdued to a simple liquid parabolic flow in a slit-pore geometry. The coarse-grained DPD procedure applies to both solvent molecules and polymer monomers, offering the pos-sibility to (i) reproduce hydrodynamic interactions while retaining a detailed view of the brush dynamics on the scale of the coarse-grained monomers; (ii) access both the polymer dynamics, influenced by the imposed flow, and the flow field, perturbed by the presence and motion of the brush.Recent studies of polymer brushes under flow [22][23][24] have highlighted an unexpected behavior in the velocity profile in the vicinity of the brush surface. These studies have reported that the velocity field reverses on increasing the flow field and have tentatively associated such result to the peculiar dynamics of the single polymer undergoing a cyclic motion of stretching, elongation and recoiling.…”
mentioning
confidence: 99%
“…Recent studies of polymer brushes under flow [22][23][24] have highlighted an unexpected behavior in the velocity profile in the vicinity of the brush surface. These studies have reported that the velocity field reverses on increasing the flow field and have tentatively associated such result to the peculiar dynamics of the single polymer undergoing a cyclic motion of stretching, elongation and recoiling.…”
mentioning
confidence: 99%